Management of Vipadika (Palmo-Plantar Psoriasis) by Ayurveda (International Journal of Ayurveda and Pharma Research, 2023)
An immune-mediated condition known as psoriasis causes persistent skin inflammation. Palmoplantar psoriasis, a kind of psoriasis that is difficult to cure, affects about 5% of all psoriasis patients. In Ayurveda, all skin conditions are referred generally under the term ‘Kushtha’. One such illness that has been classified as Kshudra Kushta is called Vipadika and is marked by symptoms like Pani-pada Sphutan (Fissure in the palms and soles) and Teevra vedana (with great pain). The main causes of its expression include vitiation of Vata, Kapha, and Pitta/Rakta. In present case report, a 54 years female patient presented in OPD 2 of Sane Guruji Rugnalaya, Hadapsar, Pune, with complaints of dryness and cracking of both soles associated with itching and pain for 1 year and was treated with oral medicines and external application of Gandharva Haritaki and Gorakhmundi Ghrita Siktha respectively. After complete treatment of 30 days, there was complete remission in the symptoms and there is no recurrence till date. From the current case report, it can be inferred that Vipadika (palmo-plantar psoriasis) can be successfully treated with the appropriate Ayurveda medications